Dislocation emission caused by different types of nanoscale deformation defects in CdTe - Babentsov, V.N.; Boyko, V.A.; Gasan-zade, S.G.; Shepelski, G.A.; Stariy, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Dislocation-related defects induced by dislocation motion in p-CdTe were
studied. Generation of “fresh” dislocations from the indented point of the CdTe (100),
(110), and (111) surfaces at room temperatures was visualized by chemical etching and
low temperature photoluminescence in a mapping regime. The crystallographic
orientation of the dislocation rosettes of macroscopic plastic deformation lines was
analyzed on the (100), (110), and (111) surfaces.